Physiological responses and antibiotic-degradation capacity of duckweed (Lemna aequinoctialis) exposed to streptomycin - Huang, Weijuan; Kong, Rui; Chen, Lijun; An, Yuxing (Frontiers in Plant Science, 2022)
Aquatic plants are constantly exposed to various water environmental pollutants. Few data on how antibiotics affect duckweed health and its removal ability. The aim of this study was to investigate the impact of streptomycin on the physiological change and uptake capability in duckweed (Lemna aequinoctialis) after exposure at different time points (0, 5, 10, 15 and 20 days). Duckweeds were exposed to streptomycin at a range of concentrations (0.1-10 mM). Results indicated that the high streptomycin concentrations (≥1 mM) resulted in a lower duckweed biomass (21.5-41.5%), RGR (0.258-0.336 g d−1), decrease in total Chl and increase in carotenoids. Antioxidative enzymes, including CAT (18-42.88 U mg protein-1), APX (0.41-0.76 U mg protein-1), and SOD (0.52-0.71 U mg protein-1) were found to accumulate in the streptomycin groups in comparison to the control group. The significant reduction (72-82%) in streptomycin content at 20 d compared to the control (40-55%) suggested that duckweed has a high ability in removing streptomycin. Transcriptome analysis showed that the secondary metabolic pathways including phenylpropanoid biosynthesis and flavonoid biosynthesis were significantly upregulated in the streptomycin setup compared to the control. Therefore, our findings suggested that duckweed can contribute to the streptomycin degradation, which should be highly recommended to the treatment of aquaculture wastewater and domestic sewage.